A color image encryption and decryption scheme based on extended DNA coding and fractional-order 5D hyper-chaotic system - Meng, Fan-Qi; Wu, Gang (Expert systems with applications, 2024)
With the advancement of information technology, the security of digital images has become increasingly important. To ensure the integrity of images, this paper presents a novel color image encryption and decryption architecture. Firstly, a fractional-order five-dimensional hyper-chaotic system (F5DHS) is proposed and used to generate chaotic sequences for permutation and diffusion processes. Secondly, the extended DNA encoding scheme is employed to generate more DNA encoding rules and four DNA computation methods are used to improve the security of the encryption scheme. Thirdly, a blocked image encryption method is designed to divide the color image into sub-blocks and then determine the DNA encoding, DNA decoding and DNA arithmetic rules for each sub-block based on chaotic sequences. Finally, the results of simulation experiments and security analysis show that the color image encryption algorithm has good encryption performance, a large secret key space, and strong robustness to noise and data loss attacks, indicating that the proposed encryption algorithm can effectively protect the secure communication of digital images.